DEVELOPMENT OF A MOBILE-BASED TRANSPORTATION AND HOTEL TICKET BOOKING INFORMATION SYSTEM AT TIKET EXTRA - Arief Hermawan; Shafira Nur Alfiah (Jurnal Riset Informatika, 2025)
The development of information and communication technology has had a major impact on various aspects of human life, including transportation and tourism. This study aims to develop a mobile-based transportation and hotel ticket booking information system integrated through the Tiket Extra application. This application is designed to make it easier for users to search for travel schedules, compare prices, and make transactions efficiently without time and place restrictions. The research method used is Research and Development (R&D) with a Waterfall model, which includes needs analysis, system design, implementation, and testing to produce an optimal and functional system. The system is integrated with Midtrans as a payment gateway to support secure, fast, and accurate digital payment processes. Testing using the Blackbox Testing and Usability Testing methods showed that all functions worked well and were responsive. Overall, the Tiket Extra application has proven to be effective in significantly improving user convenience, agent operational efficiency, and system service quality.